Decreased level of cytotoxic T lymphocyte antigen-4 (CTLA-4) in patients with acute immune thrombocytopenia (ITP). Issue 4 (October 2015) - Zhu, Feng; Qiao, Jianlin; Cao, Jiang; Sun, Hai-ying; Wu, Qing-yun; Sun, Zeng-tian; Zhao, Kai; Sang, Wei; Qi, Kun-ming; Zeng, Ling-yu; Li, Zhen-yu; Xu, Kai-lin
Abstract: Introduction: Previously, we demonstrated the importance of T-cell immune response cDNA 7 (TIRC7) in acute immune thrombocytopenia (ITP). As the downstream molecule of TIRC7, cytotoxic T lymphocyte antigen-4 (CTLA-4) has been verified its negative regulation of acute ITP. This study aimed to investigate the exact role of CTLA-4 and its relationship with TIRC7 in acute ITP. Patients and methods: 37 patients with acute ITP were enrolled and received dexamethasone (40 mg/day) for 4 consecutive days. Patients who had platelet counts more than 50 × 10 9 /L or less were defined as responders or non-responders after treatment. The plasma, protein and mRNA levels of CTLA-4 and TIRC7 were monitored by ELISA, western blot and q-PCR, respectively. Results: After high-dose dexamethasone therapy, CTLA-4 levels were significantly elevated not only in acute ITP patients (P < 0.001; P < 0.0001) but also in acute ITP responders (P < 0.0001; P < 0.0001). The levels of CTLA-4 were negatively correlated with the levels of TIRC7 before and after treatment; IFN-γ (Th1), IL-17 (Th17) and IL-22 (Th22) levels were all elevated, which were decreased after treatment not only in patients with acute ITP (P < 0.01) but also in acute ITP responders (P < 0.01). Conclusions: CTLA-4 level might reflect treatment efficacy and it might be associated with the pathogenesis of acute ITP. Highlights: CTLA-4 level was decreased in acute ITP patients before treatment. CTLA-4 levels were elevated in acute ITP patients and acute ITP responders. CTLA-4 level was negatively correlated with TIRC7 before and after treatment. The level of CTLA-4 might reflect treatment efficacy in patients with acute ITP.